Co wynika z badań opartych na dowodach dla dalszego rozwoju nauk społecznych? - Kowalik, Stanisław (Człowiek i Społeczeństwo, 2020)
Global social order calls for more and more knowledge of applicable character. As a result, medicine developed certain procedures known as evidence-based research and evidence-based practice. Both procedures are promoted with great intensity in the domain of social sciences. The article demonstrates that such a type of modernisation may pose a threat to social sciences and their development. An alternative model of conducting research in the field of social sciences has been presented, which would guarantee an increase in the regulatory scientific knowledge in relation to the practice and which, at the same time, would protect social sciences against excessive political and economic interference in its further development.